An integrated model for a class of sourcing problem using multiple regression analysis and analytical hierarchy process. (5th April 2010) - Mathiyalagan, P.; Punniyamoorthy, M.; Parthiban, P.
In the current dynamic market conditions with ever-rising competition and increasing pressures, it has been suggested that supplier selection is an issue of paramount importance to any company because improper selection of suppliers might lead to numerous problems that affect the company's overall growth. Selection of the right supplier from number of alternatives in the market is a complicated multicriteria decision-making process, which includes many quantitative as well as qualitative criteria. Even though there are umpteen number of supplier selection models available in the literature, in this paper, we have made an attempt to develop a new composite model taking into consideration the criteria which influence the selection of suppliers in the current scenario using factor analysis, multiple regression analysis and analytic hierarchy process (AHP) technique.